キタゾウアザラシ ノ チョウキ センスイ キロク - 内藤, 靖彦; ナイトウ, ヤスヒコ; Boeuf, Burney J. Le; 浅賀, 朋宏; アサガ, トモヒロ; Huntley, Anthony C.; Naito, Yasuhiro; Asaga, Tomohiro (1989)
P(論文) 南極アザラシの冬季潜水行動を知るために開発した長期潜水記録計の現場実験を, 回収が容易なキタゾウアザラシ(Mirounga angustirostris)を用いて行った。現場実験はキタゾウアザラシの連続的な深い潜水行動を知ることを主要な目的としてカリフォルニア, アニュ・ノエボ海岸で行った。1987年2月繁殖終了後の雌の成獣に記録計を装着し, 換毛のため再上陸した5月に記録計の回収を行い, 潜水行動記録として初めて73日間におよぶ長期連続記録を得た。潜水回数は, 73日間5024回であり, 1時間平均2.9回の潜水を行った。全潜水の平均深度は463.9±147mであり, 平均潜水時間は17.1±3.4分であつた。最大潜水深度と最大潜水時間は, 934mと33.5分であつた。最大潜水深度は実測された鰭脚類の深度としては最も深い記録であった。潜水は初めの4日間は深度を徐々に増し, 500m深度に達すると安定した。しかし, 潜水深度は昼夜で変わり, また約20日単位でも変化した。潜水時間は長期にも安定していた。ESI (Extended Surface Interval)直後の潜水は非常に浅い潜水から再開され, 数回の深度を増す潜水を経て通常の深度に達した。以上の実験の結果, 本記録計は装着による動物行動への影響がないことが判明し, 南極アザラシでも有効に利用できることがわかった。 Seventy-three days long diving record of an adult female northern elephant seal (Mirounga angustirostris) was obtained using the long-term time depth recorder which was developed for Antarctic seal research by the National Institute of Polar Research, Tokyo. It was observed that the female northern elephant seal dived to a great depth continuously for a long period. It dived 5024 times during 73 days, 2.9 times per hour on the average. The mean dive depth and duration were 463.9±147m and 17.1±3.4min, the maximum values being 934m and 33.5min. The dive depth increased gradually on the first 4 days. After that, it fluctuated diurnally, while the dive duration remained rather stable. Following the extended surface intervals (ESIs : defined as surface intervals longer than 10min) dives were shallow but the depth increased gradually. departmental bulletin paper